A confiabilidade do transporte coletivo urbano em corredores estruturais de ônibus - Silva, Thais Cristina Cunha e (2010)
The aim of this work is to evaluate the reliability of the urban public transport using as a study case the bus structural corridor in the João Naves de Ávila Avenue, one of the main avenues in Uberlândia, MG, Brazil. Two softwares, Simulation and Assignment of Traffic in Urban Road Networks SATURN and Dynamic Route Assignment Combining User Learning and Microsimulation DRACULA, both developed by the University of Leeds UK, were used to simulate and conclude about the influence of the deployment of the corridor on the bus route. Here it is presented an analysis on the reliability for the public transport along the avenue, where a bus-only lane and thirteen boarding and alighting stations were built, through indicators such as travel time, punctuality and regularity, among others. Through the simulation of various scenarios, this work also presents an analysis on how reliability indicators were affected by the proposed changes. Finally, a comparison between the travel time before and after the construction of the bus corridor allowed a conclusion to be reached on the actual benefits brought on by the deployment of a structural bus corridor in medium sized cities.